2006
DOI: 10.1007/s00330-006-0174-9
|View full text |Cite
|
Sign up to set email alerts
|

Drug-sensitive tuberculosis, multidrug-resistant tuberculosis, and nontuberculous mycobacterial pulmonary disease in nonAIDS adults: comparisons of thin-section CT findings

Abstract: The aim of this work was to compare thin-section CT (TSCT) findings of drug-sensitive (DS) tuberculosis (TB), multidrug-resistant (MDR) TB, and nontuberculous mycobacterial (NTM) pulmonary disease in nonAIDS adults. During 2003, 216 (113 DS TB, 35 MDR TB, and 68 NTM) patients with smear-positive sputum for acid-fast bacilli (AFB), and who were subsequently confirmed to have mycobacterial pulmonary disease, underwent thoracic TSCT. The frequency of lung lesion patterns on TSCT and patients' demographic data wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
46
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 21 publications
9
46
0
3
Order By: Relevance
“…In Nepal, levels of drug resistance are very high, with nearly 14.7% of new patients resistant to at least one drug 2 Previous treatment of tuberculosis has been consistently reported as the risk factor within various clinical conditions and populations. [4][5][6][7][8][9][10] The present study also revealed that previous treatment of tuberculosis was strongly associated with MDR TB OR =2.799 (95 % CI 1.159 to 6.667) (p=0.020).According to the National Tuberculosis Programme's Nepal National Survey in 2007, MDR among new cases of TB is 2.9% and MDR among previously treated cases is at 11% thereby giving a ratio of approximately 4:1 for prevalence of MDR in these groups, 2 this pattern holds true in our study too. Lomtadze et.…”
Section: Discussionmentioning
confidence: 99%
“…In Nepal, levels of drug resistance are very high, with nearly 14.7% of new patients resistant to at least one drug 2 Previous treatment of tuberculosis has been consistently reported as the risk factor within various clinical conditions and populations. [4][5][6][7][8][9][10] The present study also revealed that previous treatment of tuberculosis was strongly associated with MDR TB OR =2.799 (95 % CI 1.159 to 6.667) (p=0.020).According to the National Tuberculosis Programme's Nepal National Survey in 2007, MDR among new cases of TB is 2.9% and MDR among previously treated cases is at 11% thereby giving a ratio of approximately 4:1 for prevalence of MDR in these groups, 2 this pattern holds true in our study too. Lomtadze et.…”
Section: Discussionmentioning
confidence: 99%
“…On high-resolution computed tomography all patients had characteristic findings, such as bilateral bronchiectasis combined with multiple small nodules and branching linear structures [3][4][5]. The diagnosis of NTM lung disease was made when patients met the clinical, radiographic, and microbiologic diagnostic criteria published by the American Thoracic Society [1].…”
Section: Patients and Control Subjectsmentioning
confidence: 99%
“…High-resolution computed tomography reveals characteristic multifocal bronchiectasis combined with multiple small nodules (nodular bronchiectasis) [3][4][5]. Mycobacterium avium-intracellulare complex (MAC) and Mycobacterium abscessus are the most common causes of these forms of NTM lung disease [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, MDR-TB is characterized clinically by multiple cavities at CT, young patient age at the presentation, and the presence of previous history of TB chemotherapy (6,7).…”
Section: Introductionmentioning
confidence: 99%